EOG-BASED SYSTEM FOR EYES MOVEMENT DETECTION - IBRAHIM, MUHAMMAD FAIZ (IRC, 2019)
In this study, we analysis and identify the signals and data of the Electrooculography (EOG) for the movement of the eyes by identify the potentials using the wavelet algorithm. The electrode are placed horizontal and verticle from the eyes with 1cm away from the eyes to record the movements of the eyes. The wavelet algorithm is using to determine the characteristics movement of the eyes signals because the eyes will show its characteristics when its moving by see the signal since the energy of the eyes is the important parts in signal analysis. The eyes will move in a four direction which is upward,downward,left and right and all the movement of the eyes data will be recorded. The energy distribution from the eyes in a change of time and frequency need to be compare by using the Wavelet Transform(WT) to analysis the signal and data of the eyes movement. Then, wavelet scalogram need to be plotted in order to display the different of the percentages of the energy from each wavelet coefficient for the movements of the eyes. The result will proved that the change of EOG will shows the different of the signals energy with the different scale for the eyes such as left with scale 6(8-16Hz), right with scale 8(2-4Hz),downward with scale 9(1-2Hz) and upward with scale 7(4-8Hz).